2021
DOI: 10.2196/27977
|View full text |Cite
|
Sign up to set email alerts
|

Factors to Effective Telemedicine Visits During the COVID-19 Pandemic: Cohort Study

Abstract: Background With COVID-19 there was a rapid and abrupt rise in telemedicine implementation often without sufficient time for providers or patients to adapt. As telemedicine visits are likely to continue to play an important role in health care, it is crucial to strive for a better understanding of how to ensure completed telemedicine visits in our health system. Awareness of these barriers to effective telemedicine visits is necessary for a proactive approach to addressing issues. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Within the Alabama Medicaid population, telehealth services have proven to be extremely viable and have withstood the large-scale availability of vaccines to continue to be a modality of choice for health care in both rural and urban areas. Telemedicine is likely to continue to play an integral role in health care, and as a first step toward increasing the use of telemedicine, health care systems should focus on improving patient portal usage for better access to telemedicine services [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the Alabama Medicaid population, telehealth services have proven to be extremely viable and have withstood the large-scale availability of vaccines to continue to be a modality of choice for health care in both rural and urban areas. Telemedicine is likely to continue to play an integral role in health care, and as a first step toward increasing the use of telemedicine, health care systems should focus on improving patient portal usage for better access to telemedicine services [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53][54] • The literature describes a wide variety of clinician-facing, sociotechnical implementation strategies, including securing and organizing human resources (e.g., clinician champions); developing guidelines, standard scripts, and best practices; offering trainings and clearly communicating evolving processes and resources; and leveraging technological resources. [47][48][49][50][51][52][53]55 • The patient-facing initiatives reported in the literature are limited to technological training and support, with an emphasis on mitigating the risk of digital health disparities. [47][48][49][50]52,[55][56][57][58][59][60][61][62] Developing and deploying portal tools to respond to COVID-19…”
Section: Developing Deploying and Evaluating New Care Processesmentioning
confidence: 99%
“…[47][48][49][50][51][52][53]55 • The patient-facing initiatives reported in the literature are limited to technological training and support, with an emphasis on mitigating the risk of digital health disparities. [47][48][49][50]52,[55][56][57][58][59][60][61][62] Developing and deploying portal tools to respond to COVID-19…”
Section: Developing Deploying and Evaluating New Care Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In behavioral health settings, patient portals have been shown to increase a sense of patient autonomy, improve patient activation, and decrease administrative inefficiencies [ 17 , 18 ]. A recent study in a large health system across multiple specialties has also demonstrated patient portal activation is associated with increased patient ability to complete telemedicine visits [ 19 ]. Furthermore, video-based appointments performed directly through electronic medical record (EMR)–based patient portals such as MyChart provide an additional layer of security compared to separate virtual platforms such as Doximity or Skype [ 15 ] and have the advantage of closer integration with the patient’s medical record, which may help with documentation and billing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%